2019
DOI: 10.1016/j.ijid.2018.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of the E6/E7 mRNA-based Optimygene HR-HPV RT-qDx assay for cervical cancer screening

Abstract: Pap smear and high-risk human papillomavirus (HR-HPV) DNA testing are the most widely applied methods for cervical cancer screening, but both methods are limited by their low specificity and lack of association with patient prognoses. The aim of this study was to compare the clinical and prognostic significance of HPV E6/E7 mRNA as an early biomarker with cytology and HPV DNA detection in cervical cancer screening. Methods: This study evaluated the performance of the Optimygene HR-HPV RT-qDx assay, which is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…On top of this, the reported AU-ROC curve by six of the articles [51,[58][59][60][61][62] varied from 63.8 to 90.9% which reflects the usefulness of the test in discriminating women having CIN2 + . In our review 8 studies [39,[51][52][53][54][55][56][57] reported the agreement between HPV-E6/E7 mRNA and HPV-DNA testing for the detection of cervical lesions at 77.6-92.5%. Compared to DNA-based tests (the most common one was Digene Hybrid Capture 2 HPV DNA test) which indicate only the presence or absence of the virus, detecting HPV E6/E7 mRNAs gives more insight into viral activity and by implication, clinical relevance (correlate better with the severity of the lesion).…”
Section: Discussionmentioning
confidence: 84%
“…On top of this, the reported AU-ROC curve by six of the articles [51,[58][59][60][61][62] varied from 63.8 to 90.9% which reflects the usefulness of the test in discriminating women having CIN2 + . In our review 8 studies [39,[51][52][53][54][55][56][57] reported the agreement between HPV-E6/E7 mRNA and HPV-DNA testing for the detection of cervical lesions at 77.6-92.5%. Compared to DNA-based tests (the most common one was Digene Hybrid Capture 2 HPV DNA test) which indicate only the presence or absence of the virus, detecting HPV E6/E7 mRNAs gives more insight into viral activity and by implication, clinical relevance (correlate better with the severity of the lesion).…”
Section: Discussionmentioning
confidence: 84%
“… 29 30 Nowadays various studies are being done on the detection of HPV E6/E7 mRNA expression by different methods including both quantitative and qualitative. A study done by Wang et al 31 evaluated the performance of the Optimygene HR-HPV RT-qDx assay, which is an HPV E6/E7 mRNA-based assay, to detect 16 HR-HPV subtypes, concluded that the higher specificity and positive predictive value of this assay are valuable for predicting insignificant HPV DNA infections among patients with a borderline cytological diagnosis. Recently, a study done by Liu et al 32 on quantitative HPV E6/E7 mRNA assay using QuantiVirus HPV E6/E7 mRNA assay (Kodia, Henan, China) to compare the expression levels of HPV E6/E7 mRNA in HSIL and LSIL showed that the median E6/E7 mRNA copy number in HSIL (median, 14,684 copies/mL) was far higher than that in LSIL (median, 936.00 copies/mL) ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Constant overexpression of E6 and E7 leads to the development of cervical intraepithelial neoplasia (CIN) (8-10). Previous studies report that E6/E7 mRNA detection has a higher clinical speci city for detecting high-grade lesions compared to DNA-based tests but a lower sensitivity (11,12). Also, E6/E7 mRNA test results have a signi cant clinical predictive value and are more consistent with cytology and histology ndings compared to DNA-based tests (13).…”
Section: Introductionmentioning
confidence: 95%